Relationships and sexuality education topics taught in Western Australian secondary schools during 2014. Issue 4 (4th July 2017) - McKay, Erin; Vlazny, Carl; Cumming, Steven
Abstract: This paper reports on findings from the first Western Australian Survey of Educators of Sexuality Education, which aimed to assess the state of relationships and sexuality education (RSE) in the state of Western Australia. Key findings show that secondary school teachers provided more hours of RSE instruction than the national average. However, they mainly taught curriculum topics such as Abstinence from Intercourse until Married, Effects of Alcohol/drug Use on Decision-making, Puberty, and Sex and Ethics (respectful relationships). The least taught subjects included Sexually Transmitted Infections (STIs) and HIV/AIDS, Birth Control, the Impact of Media on Sexual Identity and Sexual Orientation. These findings are of concern when one considers that nationally, Western Australia has higher rates of STIs among young people aged 15–24 years and teenage pregnancies, than other parts of the country. Results from the survey can be used to form a baseline measure ahead of the roll-out of the Australian Curriculum, which includes RSE as a focus area, and the new Western Australian Curriculum for Health and Physical Education.